(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the results of treatment of biradial forearm fractures by surgical method combined with bone plate and screw, based on the following criteria: bone healing rate, level of functional recovery, and postoperative complications. Research subjects and methods: 114 patients aged 16 years and older were diagnosed with biradial forearm fractures, treated with surgical method combined with bone plate and screw at Thong Nhat Hospital from March 2020 to March 2024. Results: 100% of patients had bone healing with an average bone healing time of 12.00 ± 0.14 months. According to the Anderson scale, 87.72% of patients had very good results; 10.53% had good results, and 1.75% had average results. Near complications: superficial wound infection accounted for 3.51%. Long-term complications: 14.04% of patients felt mild pain when the weather changed and felt the screws and plates under the skin. Conclusions: Treatment of closed fractures of the two shafts of the forearm by surgery to fix the bone and screws ensures good anatomical recovery, firmly fix the fracture and maintain the correction results, so early exercise is recommended after surgery with very low complication rate.